A rare case of myiasis in a woman with genital prolapse - Kaur, Prabhleen; Ranjan, Rita; Goyal, Ritu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Myiasis is an infestation by dipterous larva that thrives on host’s living or necrotic tissue and cause massive tissue infection. We present a case of myiasis in a 65-year-old multiparous lady with procidentia. Her examination revealed a big excavatory ulcer on dependent part and cervix indwelled with maggots. About 40 to 50 such maggots were subsequently manually removed with a forceps. After conservative management, definitive surgical treatment for prolapsed uterus was done after healing of the ulcer, within three months. It is a very rare case as only a few reports have been previously published in literature.